STUDI LITERATUR: PENGARUH TINGKAT PENDIDIKAN ORANG TUA TERHADAP PRESTASI BELAJAR SISWA - Ariyani, Silvia; Purnomo, Heru; Lukitoaji, Beny Dwi (Universitas Borneo Tarakan, 2024)
The level of parental education is the lack of parental involvement in accompanying the child's growth and development, poor parenting, and parents' difficulties in meeting children's educational needs. Therefore, through this study want to find out how much influence the level of parental education on student achievement. This study uses a literature study method by reading then recording and understanding, analyzing, and comparing one or other things related to the influence of education level on children's learning achievement. The results of the study showed that the level of parental education affected the achievement of students with the moderate category. In addition, children's achievement also affects factors between individuals.